The Validity of Interfaith Marriages According to MA No. 1400K/Pdt/1986 Perspectives on Islamic Jurisprudence - Makdura, Siti Kurniawati; Juhanis, Hasan Bin; Rapung, Rapung (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2024)
This research discusses the law on interfaith marriage according to the Supreme Court No. 1400K/Pdt/1986 and the perspective of Islamic jurisprudence. The method used in this research is the library research method, namely research by studying and analyzing data obtained from library sources such as books, papers, articles, journals and so on which relate to the law of interfaith marriage, so that you will get exact data. Then the data was copied and compiled into a thesis after careful research. The results of this research can be concluded that, the first: There is not a single regulation, be it religious regulations or legislation that allows or requires marriages of different religions. Because the Supreme Court decision No. 1400K/Pdt/1986, does not have strong legal legality as a legal source for interfaith marriages. The second: The law on interfaith marriage is divided into several parts from the perspective of Islamic jurisprudence, namely: The law is for Muslim men to marry women from people of the book, that is, most scholars tend to allow such marriages and some of them only consider it a harbinger. The law on marriage between Muslim men and polytheist women is that the scholars agree that it is forbidden for a Muslim man to marry a polytheist woman. The law for Muslim women marrying non-Muslim men is that Islamic legal experts consider this marriage to be prohibited by Islam, whether the prospective husband is from people of the book (Jews and Christians) or adherents of other religions who have holy books such as Hinduism and Buddhism or adherents of other religions. beliefs that do not have a holy book. Muslim women cannot marry men other than those of their religion, whether from the people of the book or others under any circumstances.